Integrating West Kalimantan Local Wisdom, Educational Games, and Artificial Intelligence for Pancasila Education in Elementary Schools - Iir Nikmatul Fathonah; Syf. Rizekia Zulaikha Assegaf; Dita Septiana (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Digital transformation has created opportunities to develop more interactive and meaningful Pancasila Education; however, current digital learning practices still emphasize content delivery rather than integrating students’ cultural contexts. West Kalimantan local wisdom contains values aligned with Pancasila, including mutual cooperation, deliberation, responsibility, tolerance, and social care, which can serve as contextual learning resources. This study aims to analyze the integration of West Kalimantan local wisdom into educational games supported by digital technology and Artificial Intelligence (AI) for elementary school Pancasila Education. Using a qualitative library research approach, this study analyzed relevant literature on Pancasila Education, local wisdom, educational games, digital learning, and AI through thematic classification and conceptual synthesis. The findings indicate that cultural practices such as the Saprahan tradition, Dayak Longhouse (Rumah Panjang), Customary Deliberation, Cap Go Meh Festival, and Dayak customary forests can be transformed into educational game content to strengthen students’ understanding and practice of Pancasila values. The proposed conceptual model positions local wisdom as learning content, educational games as pedagogical strategies, and AI as adaptive technological support for creating contextual, engaging, and value-oriented learning experiences.